Demographic Data to Smart Decisions Discovery Learning with Liveworksheets in Geography Class - Nur Nadia Natasya; Yuswanti Ariani Wirahayu (Future Space: Studies in Geo-Education, 2026)
Critical thinking is very important to have, especially in 21st century learning and various aspects of life. The discovery learning model helps students including problem-solving, research, and making discoveries. Through the syntax of the discovery learning model , students are directed to independently conduct and investigate discoveries, so that they can hone critical thinking skills. This research aims to determine the significant influence of a Liveworksheet-assisted Discovery Learning model on students' critical thinking skills, specifically focusing on the topic of Population Dynamics within the geography curriculum. Quasi experiments are the methods used in research, while research design is in the form of posttest only control groups. The study involved 72 students, divided into two groups an experimental class (n=36) and a control class (n=36).The essay test given at the end of the learning process serves as a research instrument to obtain final data. Inferential analysis using an independent sample t-test yielded a significance value of p = 0.000 (p < 0.05). These results confirm that the integration of Liveworksheets within the Discovery Learning model significantly enhances students' critical thinking skills in geography. In addition, the average result of the posttest score of the experimental class was 76.22 while the control class was 65.11. From this, it can be concluded that the discovery learning model combined with liveworksheets has an effect on students' ability to think critically.